Changes in coordination and its variability with an increase in running cadence? - Hafer, J. F.; Freedman Silvernail, J.; Hillstrom, H. J.; Boyer, K. A. (Journal of Sports Sciences, 2016)
Alterations in joint mechanics have been associated with common overuse injuries. An increase in running cadence in healthy runners has been shown to improve several parameters that have been tied to injury, but the reorganisation of motion that produces these changes has not been examined. The purpose of this study was to determine if runners change their segment coordination and coordination variability with an acute increase in cadence. Data were collected as ten uninjured runners ran overground at their preferred cadence as well as a cadence 10% higher than preferred. Segment coordination and coordination variability were calculated for select thigh-shank and shank-foot couples and selected knee mechanics were also calculated. Paired t-tests were used to examine differences between the preferred and increased cadence conditions. With increased cadence, there was a decrease in peak knee flexion and a later occurrence of peak knee flexion and internal rotation and shank internal rotation. Segment coordination was altered with most changes occurring in mid-late stance. Coordination variability decreased with an increase in cadence across all couples and phases of gait. These results suggest examination of coordination and its variability could give insight into the risk of intervention-induced injury.